Description of a new species of Tomiyamichthys from Australia with a discussion of the generic name - Hoese, Douglass F.; Shibukawa, Kochi; Johnson, Jeffrey W. (Zootaxa, 2016)
Tomiyamichthys levisquama is described as a new species from the Northern Territory and Queensland, Australia from estuaries and soft bottom marine environments. It is distinctive in body and head shape, head coloration and by the absence of ctenoid scales on the body. It is compared with the related species Tomiyamichthys russus (Cantor 1849), which has ctenoid scales on the posterior part of the body. The validity of the name Tomiyamichthys over Flabelligobius is discussed, with both genera being described in the same paper, here accepting Tomiyamichthys as the appropriate name.